The Politics of Yehuda Amichai's Aesthetic Camouflage: Jerusalem and the Settler-Colonial Gaze - Odeh, Tayseer Abu (Journal of Holy Land and Palestine Studies, 2022)
Drawing on the notion of aesthetic camouflage the uses and abuses of memory and forgetfulness, this article seeks to examine and interrogate the ways in which Israel’s ‘national poet’ Yehuda Amichai (born ‘Ludwig Pfeuffer’, 1924-2000) relies heavily on the imperialist Zionist ideology to justify and legitimise the settler-colonial existence of Israel from a European and Zionist hegemonic perspective. The postcolonial image of Jerusalem, as mystified by Amichai’s poetry, signifies an apolitical and ahistorical Orientalist image of Jerusalem as being ‘a troubled sacred and mythical city’ claimed by clashing monolithic religions including Islam, Judaism, and Christianity. In other words, the systematic and historical absence of Palestinian people in Amichai’s poetry is ostensibly bound up with what Edward Said calls ‘the functional absence of ‘native people’ in Palestine’.